2021
DOI: 10.3390/app112210656
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Business Productivity by Applying Robotic Process Automation

Abstract: Digitalization has been bringing about various changes and innovations not only in our daily life but also in our business environment. In the manufacturing industry, robots have been used for automation for a long time, resulting in innovation in terms of the faster operation process and higher product quality. Robotics Process Automation (RPA) can be said to have brought this innovation in the productivity improvement of many industries into the business office. The purpose of this study is to improve busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Research has revealed positive aspects of the use of RPA and AI tools, citing time reduction, few starting investment and easy implementation (Hindel, Cabrera and Stierle 2020; Flechsig, Anslinger and Lasch 2021), but on the other hand, also the risk that the implementation is time consuming, and prone to errors (Hindel, Cabrera and Stierle 2020; Hyun et al 2021). The fact that robots create errors leads to the fact, that human beings must control their working results after the process is finished.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed positive aspects of the use of RPA and AI tools, citing time reduction, few starting investment and easy implementation (Hindel, Cabrera and Stierle 2020; Flechsig, Anslinger and Lasch 2021), but on the other hand, also the risk that the implementation is time consuming, and prone to errors (Hindel, Cabrera and Stierle 2020; Hyun et al 2021). The fact that robots create errors leads to the fact, that human beings must control their working results after the process is finished.…”
Section: Discussionmentioning
confidence: 99%
“…This refined approach to public engagement and data analysis underscores NLP's pivotal role in modernising and optimising government-citizen interactions (Wang et RPA has become a crucial instrument in streamlining the routine tasks prevalent in local government operations, particularly in the context of implementing digital transformation initiatives within smart city strategies (Sobczak & Ziora, 2021). RPA's ability to automate paperwork and repetitive administrative functions significantly alleviates staff workload (Hyun et al, 2021;Johansson et al, 2022). This automation translates into expedited processing for various administrative processes/governmental affairs procedures, such as license renewals and application processing, enhancing overall service delivery (Ranerup & Henriksen, 2019).…”
Section: Why Have Nlp and Rpa Gained Popularity In Local Governments ...mentioning
confidence: 99%
“…Additionally, the precision of automated processes reduces the likelihood of errors, ensuring heightened accuracy in data management and regulatory compliance-a vital consideration in government operations where inaccuracies can lead to substantial repercussions (Hyun et al, 2021;Sobczak & Ziora, 2021). Thus, the adoption of NLP and RPA technologies offers local governments a pathway to not only bolster operational efficiency and service quality but also promote government decisions to adapt more responsively to the dynamic needs and expectations of their citizenry, e.g., unbiased decisions, new forms of democratic participation, inclusion of users and improved working conditions for employees (Wirtz & Müller, 2019;Johansson et al, 2022;Hujran, et al, 2023).…”
Section: Why Have Nlp and Rpa Gained Popularity In Local Governments ...mentioning
confidence: 99%
“…In the beginning, the co-occurrence table had 107 codes; after the validation, we had 59 codes, which referred to nineteen papers to answer the questions. Papers removed from the study after data analysis are in [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92],…”
Section: A Phases Of Literature Review Conductingmentioning
confidence: 99%